2015
DOI: 10.1007/s13314-014-0155-9
|View full text |Cite
|
Sign up to set email alerts
|

First report of white mould caused by Sclerotinia sclerotiorum on jackfruit

Abstract: Symptoms of white mould were first observed on jackfruit (Artocarpus heterophyllus) in Rangpur, Bangladesh, during February 2012. Fluffy, white mycelia developed on the fruit surface, along with large irregular black sclerotia. Morphological characteristics and the internal transcribed spacer sequences of ribosomal DNA identified the fungus as Sclerotinia sclerotiorum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In Bangladesh, S. sclerotiorum was previously reported on hyacinth bean, marigold, jackfruit and okra ( Prova et al . , 2012 , 2014 , 2017 ; Rahman et al . , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, S. sclerotiorum was previously reported on hyacinth bean, marigold, jackfruit and okra ( Prova et al . , 2012 , 2014 , 2017 ; Rahman et al . , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lighter results of this disease can reduce the output to 30–50%, and the severe results cut output by 80% or even lead to no harvest, seriously affecting the economic benefits of planting mulberry. Previous studies have reported that sclerotiniosis is caused by Scleromitrula or Sclerotinia which is distributed worldwide and causes disease in mulberry and many other important crops 8 9 10 11 12 13 . However, the impact of mulberry genotype on the soil fungal community and the relationship with sclerotiniosis was not studied so far.…”
mentioning
confidence: 99%
“…Invasive hyphae of S. sclerotiorum intracellularly colonize host tissues while host cell death and tissue maceration originate at the center of the site of initial infection. This difficult-to-control fungus notoriously devastates global food security and recently spread to previously uninhabited geographical niches ( 64 67 ). The global infection transcriptome was investigated based on the spatial organization of invasive hyphae relative to that of the central mycelium cells.…”
Section: Transcriptomicsmentioning
confidence: 99%